Identification, functional analysis, and clinical applications of defective viral genomes - Yan, Xiaowei; Pan, Yitong; Li, Peiying; Zhu, Li; Yu, Jianhai; Shen, Chenguang; Zhang, Bao; Zhao, Wei (Frontiers in Microbiology, 2025)
Defective viral genomes (DVGs) are fragments derived from defective interfering particles (DIPs) that form during viral replication. They play important roles by interfering with complete virus replication and regulating host immune responses. Advances in high-throughput sequencing (HTS) and bioinformatic technology have significantly improved the ability to identify DIPs and DVGs. Their heterogeneity and dynamic formation mechanisms have been analyzed using long-read sequencing technologies. Both DIPs and DVGs inhibit wild-type viral proliferation by competing for viral replication resources and activating innate immune pathways such as those of retinoic acid-inducible gene 1 and mitochondrial antiviral signaling protein. This might influence infection outcomes by regulating inflammatory cytokine storms. The clinical application of DIPs and DVGs in their natural attenuated virus forms has been investigated in terms of novel vaccine design and antiviral therapy. This report systematically reviews cutting-edge detection techniques, molecular mechanisms, and translational medicine advances of DIPs and DVGs and provides a theoretical basis for developing broad-spectrum antiviral strategies based on DIPs.